To compare advantage of non-fixation versus fixation of mesh in Laparoscopic totally Extra Peritoneal (TEP) repair of inguinal hernias - Ambar Gangopadhyay; Bikash Chandra Ghosh (Asian Journal of Medical Sciences, 2018)
Background: Mesh fixation during laparoscopic totally extra peritoneal repair is thought to be necessary to prevent recurrence of infections and post-operative complications. However, mesh fixation might increase the postoperative complications and chronic pain. This study was to describe the experience of a single surgeon at R.G. Kar Medical College and Hospital performing this operation. This study evaluates the outcomes of laparoscopic hernioplasty performed with and without mesh fixation at our institution.